Factors Affecting Students’ Perception of Online Shopping - Anushia Chelvarayan; Chew Sin Jie; Yeo Sook Fern (International Journal of Entrepreneurship, Business, and Creative Economy, 2021)
In the recent time, the Internet is being used as the main source to provide us information and has been vastly exploited for our own convenience. It can be seen as a mean to provide us fun and pleasure with unlimited opportunities. Hence, online shopping is an action or activity of purchasing goods and services through the Internet. This includes people going online, logging in to a shopping website, purchasing goods and services and arranging for delivery. Besides that, the buyer either pays with credit or debit card or through third party online transfer or cash on delivery for the goods and services. The research emphasizes on factors affecting students’ perception of online shopping. It focuses on the following variables such as convenience, ease of use, usefulness, privacy and security and saves money, time and effort as the main factors in affecting a student to pursue with online purchases. The theoretical foundations for this study are Technology Acceptance Model (TAM) and Theory of Planned Behaviour (TPB). A total of 200 respondents from a private university in Malaysia participated in this research. Samples were selected using convenience sampling and the respondents answered the questionnaire via Google form and paper and pencil method. A nominal scale and Five-point Likert scale was used to design the questions in the questionnaire. Data analysis methods used in this research were Descriptive Analysis, Reliability Analysis and Multiple Regression Analysis. The data collected and also information in this research are highly beneficial and valuable to students, supervisors, academics, researchers, learning institutions, business organisations and the government as we are able to gauge and understand the factors affecting students’ perception on online shopping. However, there are some limitations as this research does not reflect the actual student population in tertiary education in Malaysia and it only focuses on four variables i.e. convenience, ease of use, usefulness, privacy and security and saves money, time and effort. There are several possibilities for future researches whereby one can focus more on other influencing factors such as trust, risk, complexity, pervasive technology usage, tech savvy future generations and many more.